The short-term effects of intravitreal aflibercept injections and dexamethasone implant on ocular hemodynamics in retinal vein occlusions - Ciloglu E; Yıldırım Celikdemir A (Dove Medical Press, 2019)
Emine Ciloglu,1 Ayse Yıldırım Celikdemir21Department of Ophthalmology, Adana City Training and Research Hospital, Adana, Turkey; 2Department of Radiology, Adana City Training and Research Hospital, Adana, TurkeyPurpose: To determine the early effects of intravitreal anti-VEGF and dexamethasone application on blood flow velocities in patients with retinal vein occlusions.Methods: The ophthalmic (OA) and the central retinal arteries (CRAs) of the affected and unaffected eyes of 21 patients with central retinal vein occlusion (CRVO), and 26 patients with branch retinal vein occlusion (BRVO) were investigated by Color Doppler imaging (CDI). Peak systolic volume (PSV), end diastolic volume (EDV), and average blood velocity (Vmean) of the CRA and OA were measured and resistive indexes (RI) were calculated at pre-injection and the 1st week and 1st month post-injection.Results: There was no statistically significant difference between the OA values for affected and unaffected eyes in the CRVO group before treatment. The CRA, EDV, and Vmean values were significantly lower in affected eyes. Blood flow velocities of both CRA and OA were not significantly different than in the fellow unaffected eyes in the BRVO group. The differences between PSV, EDV, and Vmean measurements of OA and CRA at different times pre- and post-injection in response to anti-VEGF and dexamethasone treatment in the CRVO group were significant; but there was no difference in RI value. OA blood flow velocity measurements were not statistically different post-injection in the BRVO group; however, the values of PSV and EDV of CRA decreased post-injection.Conclusion: Intravitreal anti-VEGF and dexamethasone implant may induce retinal arteriolar vasoconstriction in patients with retinal vein occlusion.Keywords: retinal vein occlusion, anti-VEGF, dexamethasone, ocular doppler ultrasonography